Accretion, Disks, and Magnetic Activity in the TW Hya Association. Issue Volume 10:Issue S314(2015) (November 2015) - Stelzer, B.; Frasca, A.; Alcalà, J.M.
Abstract: We present new photometric and spectroscopic data for the M-type members of the TW Hya association with the aim of a comprehensive study of accretion, disks and magnetic activity at the critical age of ~ 10 Myr where circumstellar matter disappears.